Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa PKn di SD - Polintan Rehulina Sembiring (Program Studi PGSD Kampus UPI di Serang, 2020)
This study aims to improve student activity and learning outcomes by applying the Numbered Heads Together (NHT) cooperative learning model. This type of research is classroom action research. Observations in this classroom action research are carried out in 2 cycles. Each cycle goes through the stages of planning, implementing, observing and reflecting. To collect data in this study, the techniques used are guided by the qualitative and quantitative research paradigms. The data in this study were analyzed using descriptive analysis. The research subjects were fourth grade students of SDN 105316 Beranti which consisted of 17 male students and 13 female students, so that the total number of students was 30 students. From the results obtained, it can be concluded that there is an increase in student learning activities by 34%, namely the percentage of students who are actively learning in cycle II (87%) is greater than in cycle I (53%), and there is an increase in student learning completeness by 36.6 %, namely the percentage of classical student learning completeness in cycle II (90%) is greater than that in cycle I (53.4%).